Analysis of the Validity and Reliability of Indonesian Vocabulary Mastery Instrument Items Using AIKEN'S Model Calculations - Kartika Rismawati (Schola, 2023)
This research is part of the research on the development of domino card learning media to improve elementary school students' mastery of Indonesian vocabulary. The purpose of this study was to determine the content validity and reliability of the items of the Indonesian vocabulary mastery instrument that had been prepared in the form of entries. The analysis of the instrument content uses Coefficient V by Aiken's while Reliability uses the Cronbach Alpha calculation. The results of this study indicate that: each item of the Indonesian vocabulary mastery instrument that has been compiled is proven to be valid, the highest with Aiken's V coefficient of 0.94. However, in this case the instrument compiled is still low in the reliability test with the Cronbach's Alpha coefficient of 0.309. So that the instrument that has been prepared needs to be revised before being used.